Aquarium with waste material / Ishten Perumal, Sarvesh Rau Somu Naidu and Kasvini Yogaraj - Perumal, Ishten; Somu Naidu, Sarvesh Rau; Yogaraj, Kasvini (Universiti Teknologi MARA, Perak, 2020)
The world generates 2.01 billion tons of municipal solid waste annually, with at least 33 percent not managed in an environmentally safe manner, (World Bank Municipal Data). Modern lifestyle has led to more acute waste problems. One of the main waste materials that can be reused is polystyrene. On the other hand, young kids nowadays want to have their own aquarium but it's much too expensive to buy one. As a solution for these 2 problems a new idea establishes. Used Polystyrene incorporated with some other used/waste material to innovate a new Waste Based Aquarium. The usability and life span of the aquarium were tested in an Aquaponics' project. Polystyrene and Waste glass collected from identified market sellers for free. Polystyrene measurements have been taken for fit in glass so that fish growth can be monitored clearly. Base model fixed with Eco- friendly glue. To enhance the polystyrene to be more stable clay collected from stream mixed Benzoin Resin Ash. Di-chloride tap water, added to the aquaponics base tank to check for any leakage. Upon completion of 7 months, we conclude that Waste Based Aquariums in aquaponics are Cost Effective, Attract the kids Reduced disposal of glass and polystyrene and Eco friendly.